2019
DOI: 10.1080/17461391.2019.1600586
|View full text |Cite
|
Sign up to set email alerts
|

A season long investigation into the effects of injury, match selection and training load on mental wellbeing in professional under 23 soccer players: A team case study

Abstract: A season long investigation into the effects of injury, match selection and training load on mental wellbeing in professional under 23 soccer players: A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 24 publications
2
28
1
Order By: Relevance
“…Such earlier case identification may better facilitate timely referral and intervention, especially among athletes at elevated risk of impaired well-being, such as injured athletes. 8 This short report extends earlier APSQ validation work by providing a range of less severe cut-off scores for mental health symptoms, while also including a female elite athlete sample. The aims of this study were to: 1.…”
Section: Open Accessmentioning
confidence: 64%
“…Such earlier case identification may better facilitate timely referral and intervention, especially among athletes at elevated risk of impaired well-being, such as injured athletes. 8 This short report extends earlier APSQ validation work by providing a range of less severe cut-off scores for mental health symptoms, while also including a female elite athlete sample. The aims of this study were to: 1.…”
Section: Open Accessmentioning
confidence: 64%
“…Professional soccer players can play up to 60 matches in a competitive season, including periods of fixture congestion where they may be required to play three matches in seven days (Carling et al, 2015). Changes in performance, injury risk and objective and subjective wellness/recovery have been assessed during a competitive season (Abbott, Brownlee, Harper, Naughton, & Clifford, 2018;Abbott et al, 2019;Slater et al, 2018). However, changes in perceptions of mental fatigue across a season have not been previously investigated, despite anecdotal evidence of players and coaches previously citing the mentally fatiguing nature of professional soccer, particularly towards the end of the season.…”
Section: Introductionmentioning
confidence: 99%
“…Amotivation was evidenced as it presented associations with the dimensions of stress and recovery in both periods. In the sports context, it is important to be aware of the player's mental health status 28 . Monitoring these variables can provide relevant information on the current psychophysiological state in which the soccer player finds himself and overtraining and amotivation can negatively impact the performance of professional soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Brink et al 27 and Meeusen et al 15 identified that players with signs of overtraining showed a drop in performance. Previous research has found alterations in mental health well-being 28 . Nevertheless, few studies have evaluated the overtraining and motivational levels throughout the whole sports season in elite players 26 .…”
Section: Introductionmentioning
confidence: 93%